Gentrification in Porto: problems and opportunities in the past and in the future of an internationally open city - Fernandes,José (2018)
The speed and scale of urban tourism growth raises new challenges to understand contemporary gentrification processes, namely for internationally open, heritage-rich medium-sized cities. Based on the case of Porto (Portugal), we explore two of such challenges. First, we claim that the concept is becoming rather diffuse and that there’s a need to consider different types of rapid urban change, namely social (of residents) and/or economic (related with activities). Second, we defend a better appreciation of history by arguing that leisure-led gentrification processes have been taking place for centuries in Porto. Third we compare 19th century British-driven gentrification processes in the city with contemporary urban change in its central district, in order to highlight the unprecedented functional change imposed by international visitors and “floating city users”, as well as a number of associated challenges in keeping diversity having in mind what local development should be about.